An Analysis of Classroom Management Conducted by the English Teacher at a Private Islamic Junior High School - Putri, Adelia Trisna; Laili, Muawwinatul (research, training and philanthropy institution Natural Aceh, 2024)
This study investigates the classroom management strategies of an English teacher at a private Islamic Junior High School in Sidoarjo, focusing on time and space management, student behavior, and instructional strategies. The research aimed to evaluate the effectiveness of these strategies in creating a conducive learning environment. Observations were conducted during two meetings on May 28 and 29, 2024, using an observation checklist based on McLeod, Fisher, and Hoover's classroom management theory. Additionally, an interview with the teacher provided further insights. The results revealed that the teacher effectively managed classroom time and space, scoring 50% in both sessions. However, student behavior management could have been more effective, with scores of 45% and 50% in the respective meetings. Instructional strategies were also limited, with scores of 40% in both meetings. The study highlights a well-organized classroom environment but points to areas for improvement, including enhancing behavior management techniques and incorporating diverse instructional strategies. The implications suggest a need for more dynamic and responsive approaches to classroom management, including integrating technology and fostering personal connections with students to improve engagement and learning outcomes.